Pengembangan Buku Ajar Akidah Akhlak untuk Meningkatkan Pemahaman Siswa Madrasah - Zainuddin Zainuddin (Jurnal Pendidikan Islam Indonesia, 2019)
Based on the development process and the test results of the target, it can be concluded as follows (1) result of this activity in the form of textbook of Akidah Akhlak for Madrasah Ibtidaiyah, (2) average learning outcomes in the final test after using textbook increased to 77.25% compared with 67.00% of average learning outcomes in the final test before using textbook. Refers to the T-test and Sig (2-tailed) test result is 0.001 after being compared with the received error rate is 0.05, the developed textbook has been effective.